Penerapan Hand Hygiene Petugas di Ruang Perawatan Stroke - Resmi Dinanti; Mira Suryani; Lilik Pranata; Bangun Dwi Hardika; M. K. Fitriani Fruitasari (Yayasan Literasi Sains Indonesia, 2022)
Hand hygiene is one of the breakers of the chain of disease transmission in hospitals, so hand hygiene is very important in room management, especially if it is carried out correctly by officers, especially in special rooms where there are patients who are bedres or partial care to total care such as in stroke care. The purpose of the study was to photograph the Application of Hand Hygiene Officers in the Stroke Treatment Room. The research method is descriptive quantitative research design to see the description of the application of hand hygiene. The sample is an officer who provides services in the stroke care room, the study was conducted in a private hospital in Palembang City, primary data collection was carried out on November 1-03 2021, with a sample of 18 people, the instrument used was an observation sheet, and the sample criteria were in accordance with with the inclusion criteria of officers on duty in the stroke care room. The results showed that there were still officers who had not applied the five moments and 6 steps of washing hands properly. Suggestions for hospital institutions gave policies to room staff in getting used to doing hand hygiene. Meanwhile, health workers must realize the importance of hand hygiene for the patient's recovery process and improve hospital services.